Perkembangan Ilmu Negara dalam Konteks Global, Tantangan dan Peluang - Wandi Pratama Putra; St. Hadijah Wahid; Nursyafiza Nursyafiza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
State science is a discipline that studies the state in various aspects, including its origins, functions, goals, and relationships with society and other institutions. This article explores the country's science development from a global perspective, highlighting the challenges and opportunities it faces in the modern era. This research examines the evolution of state theories, interactions between states and non-state actors, and the impact of globalization on the function and role of the state. In addition, this article also analyzes how technological changes and geopolitical dynamics influence the study and practice of state science. Through a multidisciplinary approach, this article aims to provide in-depth insight into the transformation of state science and its implications for public policy and governance in the 21st century.